Adsorption of heavy metal by natural clayey soil - Wawan Budianta (Journal of Applied Geology, 2015)
This study focused on the capability of Clayey soil to retain and release heavy metals. Batch experiment for sample of clayey soil was conducted with several concentrated solutions of heavy metals. The results show that the clayey soil sample may have a relatively high heavy metal retention capacity. This is particularly positive in the context of municipal waste disposal (landfills) in Indonesia Keywords: Adsorption, heavy metal, clayey soil, batch experiment